Ultrasound-Guided Proximal and Distal Tarsal Decompression: An Analysis of Pressures in the Tarsal, Medial Plantar, and Lateral Plantar Tunnels. Issue 2 (April 2021) - Iborra Marcos, Alvaro; Villanueva Martinez, Manuel; Sanz-Ruiz, Pablo; Barrett, Stephen L.; Zislis, George
Objectives. To analyze the reliability of measurements of tarsal tunnel and medial and lateral plantar tunnel pressures before and after ultrasound-guided release. Measurements taken were guided by ultrasound to improve reliability. This novel approach may help surgeons make surgical decisions. The second objective was to confirm that decompression using ultrasound-guided surgery as previously described by the authors is technically effective, reducing pressure to the tarsal and medial and lateral plantar tunnels.Methods. The study included 23 patients with symptoms compatible with idiopathic tarsal tunnel syndrome (TTS). The first step was to measure intracompartmental pressure of the tarsal tunnel, medial plantar tunnel, and lateral plantar tunnel preoperatively. The second step was ultrasound-guided decompression of the tibial nerve and its branches. Subsequently, pressure was measured again immediately after decompression in the 3 tunnels.Results. After surgery, the mean values significantly dropped to normal values. This represents a validation of effective decompression of the tibial nerve and its branches in TTS with ultra–minimally invasive surgery.Conclusions. The ultrasound-guided surgical technique to release the tibial nerve and its branches is effective, significantly reducing pressure in the tunnels and, thereby, decompressing the nerves. Level of evidence: Level IV